Long term impact of nutrient management options on yield, and nutrient uptake by soybean and soil properties under soybean (Glycine max) - wheat (Triticum aestivum) cropping system in the Indian Himalayas - DAS, SHRILA; KUMAR, N; DAS, RUMA; ADITYA, KAUSTAV (The Indian Journal of Agricultural Sciences, 2019)
Long term effect of nutrient management practices in wheat (Triticum aestivum L.) -soybean [Glycine max (L.) Merr.] cropping system were monitored after 7 years on the changes of different chemical and microbiological properties of soil (Mollisols) at Norman E Borloug Crop Research Centre, Pantnagar, Uttarakhand (Himalayan region, India). The experiment was laid out in a randomized block design with four nutrient management options with four replications with soybean variety PS 1347. Results recorded that the integrated use of organic and inorganic sources of nutrients (50% organic + 50% inorganic) showed highest grain (1.81 t/ha) and straw (3.11 t/ha) yield, and N (121.61 and 58.12 kg/ha) and P (11.85 and 13.83 kg/ha) uptake in grain and straw, respectively when compared with rest of the treatments (100% organic treatment, 100% inorganic treatment and INM (Integrated Nutrient Management) + IPM (Integrated Pest Management). The treatment 50% organic + 50% inorganic sources of nutrient also showed 56.4% significantly higher nodule number than with 100% organic treatment at 60 DAS (days after sowing) which recorded lowest nodule number (24.6/plant). Though, INM + IPM treatment was better than 100% organic treatment with respect to nodulation, yield, nutrient concentration and uptake, but microbial biomass and dehydrogenase activity were significantly higher in 100% organic treatment than the other treatments. Therefore, 50% organic + 50% inorganic treatment was found best for most of the symbiotic, plant growth and yield parameters of soybean possibly by saving water, energy and nutrient resources which would help in maintaining the sustainability of the production system over the years.